Perspectives on a Metacognitive Approach to Translation Teaching - MADOUI, Saoussen (Journal of Human Sciences, 2012)
Translation teaching methodologies ought to be revised to allow students more space to develop their own competence and take in hand their learning enterprise. The traditional approach to translation teaching seems to be void of any serious attempt to meet the requirements of a systematic development of students’ cognitive ability, which is at the core of their translation competence. In what follows is a general analysis of the way translation is taught and new perspectives on how it should be taught with a special emphasis on the role of raising students’ metacognitive awareness.